Value of Routine Voiding Cystourethrography After Renal Transplantation. Issue 1 (27th September 2012) - Margreiter, M.; Györi, G. P.; Böhmig, G. A.; Trubel, S.; Mühlbacher, F.; Steininger, R.
<x xml:space="preserve">Abstract</x> The impact of vesicoureteral reflux (VUR) on renal allograft outcomes is debatable, with small cohort studies reporting controversial results. The objective of this retrospective study was to evaluate long‐term clinical effects of early VUR in a large cohort of kidney transplant patients. Posttransplantation voiding cystourethrography was used to evaluate 646 consecutive kidney transplant recipients before discharge. The study endpoints included VUR grade, death‐censored graft or patient survival, renal function, proteinuria and occurrence of urinary tract infections (UTIs). Of the 646 recipients, 263 (40.7%) were diagnosed with VUR. VUR grade II was most common (19.8%), followed by grades III (10.2%), I (7.9%) and IV (2.8%). VUR was less common in transplantations performed by experienced compared to inexperienced surgeons (36% vs. 48%; p = 0.004). VUR did not affect death‐censored graft or patient survival and was not associated with proteinuria or occurrence of UTIs. Patients with VUR had a lower eGFR at 1 year after transplantation than did patients without VUR (60 vs. 52 mL/min/1.73 m2; p = 0.02), although this difference was not observed at 3 and 5 years after transplantation. We conclude that early VUR, a common finding among renal transplant patients, may not have a meaningful impact on long‐term transplant outcomes.